Powder for manufacturing a component by selective laser melting

CN123036170APending Publication Date: 2026-11-03SAFRAN AIRCRAFT ENGINES SAS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580024930.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-25
Filing Date
2025-03-24
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing technologies make it difficult to manufacture metal alloy components with complex shapes, and these components have insufficient mechanical properties at the high temperatures of aircraft propulsion systems, especially with excessively high coefficients of expansion, leading to wear and clearance problems.

Method used

Cobalt alloy powder prepared by atomization has a particle size distribution of D10 less than 25 μm, D50 of 20 μm to 50 μm, and D90 less than 80 μm. Components are manufactured by selective laser melting, and the mechanical properties are optimized by combining this with a heat treatment step.

Benefits of technology

Components with optimized mechanical properties at high temperatures are manufactured, including low coefficient of thermal expansion, optimized tensile strength, and resistance to fatigue, creep, oxidation, and corrosion, significantly improving component lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a powder for manufacturing a component by selective laser melting, the powder being prepared by atomizing an initial cobalt alloy comprising 22 to 45 wt% cobalt, 20 to 35 wt% nickel and 18 to 32 wt% iron, the powder having a particle size distribution with a D10 size of less than 25 μm, a D50 size of 20 to 50 μm and a D90 size of less than 80 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a powder for manufacturing components by selective laser melting and a method for manufacturing components using said powder. The invention also relates to components obtained by said method and an aircraft comprising one or more components obtained by said method. Background Technology

[0002] The propulsion system of an aircraft includes metal alloy components that are subjected to extreme operating conditions, especially temperatures that can reach 1000°C, such as turbine blades and nozzles. Therefore, these metal alloy components must have mechanical properties that can withstand these extreme operating conditions, such as sufficient tensile strength and good resistance to fatigue, creep, oxidation, and corrosion.

[0003] These components can be manufactured, for example, using forging or casting processes with metals or alloys. However, these methods cannot produce components with complex shapes. Furthermore, components obtained by forging have insufficient mechanical properties.

[0004] To manufacture metal parts with complex shapes, the known method of laser beam melting (LBM) can be used. Using this method, a bed of metal alloy powder is melted by a laser beam to obtain a solid part. This method can be performed, for example, on Inconel 718 or Hastelloy X alloys.

[0005] However, the components obtained from these alloys lack satisfactory mechanical properties, and in particular, have an excessively high coefficient of thermal expansion at the operating temperatures of the aircraft propulsion system. This necessitates a large clearance between these components and other parts of the propulsion system, leading to significant wear on the components. Summary of the Invention

[0006] One object of the present invention is to manufacture metal alloy components for aircraft propulsion systems, which have complex shapes and optimized mechanical properties at the operating temperature of the propulsion system.

[0007] For this purpose, the first subject of the present invention is a powder for manufacturing parts by selective laser melting, said powder being prepared by atomizing an initial cobalt alloy comprising 22 wt% to 45 wt% cobalt, 20 wt% to 35 wt% nickel, and 18 wt% to 32 wt% iron, said powder having the following particle size distribution: D10 size is less than 25 μm. The D50 size ranges from 20 μm to 50 μm, and The D90 size is less than 80 μm.

[0008] This powder, particularly due to its particle size distribution, enables the manufacture of solid parts with optimized mechanical properties. Advantageously, these optimized mechanical properties are maintained even at extremely high temperatures, potentially reaching 750°C, preferably up to 650°C. Solid parts obtained from this powder can, in particular, have a lower coefficient of thermal expansion than parts typically manufactured, for example, by selective laser melting from Hastelloy X or Inconel 718. These solid parts also exhibit optimized tensile strength and good resistance to fatigue, creep, and / or oxidation and corrosion.

[0009] The initial alloy may additionally contain 2.0% to 4.0% by weight of chromium, 2.0% to 4.0% by weight of niobium, and 4.0% to 7.0% by weight of aluminum.

[0010] For example, the initial alloy may contain: by weight percentage, 2.5% to 3.5% chromium, 26.0% to 30.0% nickel, 24.0% to 27.0% iron, 2.5% to 3.5% niobium, 5.0% to 6.0% aluminum, and 33.5% to 42.5% cobalt, The second subject of this invention is a method for manufacturing metal alloy parts, the method comprising the following steps: S1: Powder is prepared by atomizing an initial cobalt alloy comprising 22% to 45% cobalt, 20% to 35% nickel, and 18% to 32% iron, wherein the powder has the following particle size distribution: D10 size is less than 25 μm. The D50 size ranges from 20 μm to 50 μm, and D90 dimensions are less than 80 μm; S2: Solid parts are obtained by selective laser melting of powder.

[0011] Using this method, it is possible to manufacture solid parts that may have complex shapes and optimized mechanical properties. Advantageously, these optimized mechanical properties are maintained even at extremely high temperatures, potentially reaching 750°C, preferably up to 650°C. Solid parts obtained by this method can, in particular, have a lower coefficient of thermal expansion than parts typically manufactured by selective laser melting using, for example, Hastelloy X or Inconel 718. The solid parts can also exhibit optimized tensile strength and good resistance to fatigue, creep, and / or oxidation and corrosion.

[0012] In this specification, weight percentages refer to the weight percentage of a compound relative to the total weight of the composition containing that compound. For example, the weight percentage of cobalt in the initial alloy refers to the weight percentage of cobalt relative to the total weight of the initial alloy.

[0013] In this specification, "solid part" refers to an integrated solid part.

[0014] Preferably, the powder may have the following particle size distribution: D10 dimensions range from 10 μm to 25 μm. The D50 size ranges from 25 μm to 40 μm, and The D90 size ranges from 40 μm to 70 μm.

[0015] In a preferred embodiment, powder preparation includes: atomizing the powder, followed by sorting the powder to obtain a desired particle size distribution. Sorting is performed by sieving or using a size classifier. Powder particles that do not have the desired size are removed.

[0016] Atomization is a method that can achieve good powder quality, especially optimizing sphericity.

[0017] Powder preparation The powder is prepared by atomizing the initial liquid alloy to obtain powder, preferably by gas atomization. It is then sorted to obtain the desired particle size distribution.

[0018] The aforementioned powder particle size distribution provides good powder bed density and optimized powder flowability. Furthermore, this particle size allows for the limitation of fusion stresses, thereby restricting cracking of the alloy. In particular, this particle size allows for the limitation of residual stresses, which are stresses generated when the material solidifies and thus contract when subjected to tensile force on either side of the material. Cracks can then appear in the material.

[0019] Therefore, cracking may occur during alloy solidification, but it may also occur during stress-relief heat treatment.

[0020] Furthermore, the calibrated particle size ensures that the parts manufactured using the parameters described above have optimized mechanical strength. In particular, the manufactured parts are dense and have few or no defects.

[0021] “D 50 The "median" size refers to the size when the cumulative function F(D) is 50%. 10 "Size" refers to the size when the cumulative function F(D) is 10%. 90"Size" refers to the size when the cumulative function F(D) is 90%. The cumulative function F(D) is defined by the following formula:

[0022] in: f(D) is the granularity distribution expressed in terms of quantity, and D i It refers to the size category.

[0023] Size D 10 D 50 and D 90 It can be determined according to standard ISO 13320 or ASTM B822.

[0024] The powder preferably comprises particles of a generally spherical shape. In this document, when the particle shape is substantially spherical, its dimensions are given as equivalent sphere diameters. The shape of the powder particles can be determined according to standards ISO 13320 or ASTM B822.

[0025] The initial alloy contains 22% to 45% cobalt, preferably 25% to 42% cobalt, and more preferably 27% to 41% cobalt.

[0026] The initial alloy additionally contains 20% to 35% by weight of nickel, preferably 23% to 34% by weight of nickel, and more preferably 25% to 31% by weight of nickel.

[0027] The initial alloy further comprises 18% to 32% by weight of iron, preferably 20% to 31% by weight of iron, and more preferably 23% to 28% by weight of iron.

[0028] The initial alloy may additionally contain 2.0% to 4.0% by weight of chromium, preferably 2.2% to 3.2% by weight of chromium.

[0029] The initial alloy may additionally contain 2.0% to 4.0% wt% niobium, preferably 2.2% to 3.2% wt% niobium.

[0030] The initial alloy may further contain 4.0% to 7.0% by weight of aluminum, preferably 4.5% to 6.5% by weight of aluminum, and more preferably 4.8% to 6.2% by weight of aluminum.

[0031] The alloy may also contain trace amounts of compounds selected from manganese, silicon, titanium, copper, and mixtures thereof. These compounds are present in the alloy in amounts of less than or equal to 1% by weight, preferably less than or equal to 0.7% by weight.

[0032] The initial alloy may also contain unavoidable impurities selected from carbon, phosphorus, sulfur, chromium, boron, tantalum, oxygen, nitrogen, hydrogen, and mixtures thereof. The content of these unavoidable impurities in the alloy is less than or equal to 0.1% by weight, preferably less than or equal to 0.07% by weight.

[0033] For example, the initial alloy used could be Inconel 783. The composition of Inconel 783, by weight percentage, is as follows: 2.5% to 3.5% chromium, 26.0% to 30.0% nickel, 24.0% to 27.0% iron, 2.5% to 3.5% niobium, 5.0% to 6.0% aluminum, and The balance is cobalt; 0.003% to 0.012% boron 0.03% maximum carbon 0.50% max manganese 0.50% max manganese 0.015% max phosphorus 0.005% max sulfur 0.1% to 0.4% titanium 0.50% max copper It is possible that the initial alloy may be free of oxygen, nitrogen, and / or hydrogen.

[0034] The powder obtained by atomizing the initial alloy can have the same composition as the initial alloy. Same composition means that the weight percentage of each element in the initial powder varies by ±2% relative to the weight percentage of the same element in the initial alloy.

[0035] The composition of the powder may differ from that of the initial alloy due to the presence of oxygen, nitrogen, and / or hydrogen, or its weight percentage may be increased if the initial alloy already contains oxygen, nitrogen, and / or hydrogen. The content of oxygen, nitrogen, and / or hydrogen, or an increase in its weight percentage, may be particularly attributable to the atomization process.

[0036] Selective laser melting of powder The powder was selectively laser-melted.

[0037] Melting is performed using a laser power of 100 watts to 1000 watts, preferably 120 watts to 350 watts, and more preferably 150 watts to 300 watts.

[0038] The laser scanning speed for obtaining the melt can be from 700 mm / s to 4600 mm / s, preferably from 800 mm / s to 1450 mm / s, and more preferably from 900 mm / s to 1300 mm / s.

[0039] The laser power and scanning speed are selected specifically to allow sufficient energy to achieve melting while limiting residual stress and cracking. Therefore, the selective laser melting method is optimized and allows for the efficient production of desired solid parts.

[0040] The thickness of the powder layer to be melted can be from 10 μm to 100 μm, preferably from 15 μm to 60 μm, and more preferably from 20 μm to 40 μm. Different powder layers melted successively by laser melting can have the same or different thicknesses, preferably the same thickness.

[0041] During scanning, the laser track width can be from 40 μm to 300 μm, preferably from 45 μm to 250 μm, and more preferably from 50 μm to 200 μm.

[0042] During scanning, the stripe width can be from 0.5 mm to 300 mm, preferably from 1.2 mm to 22 mm, and more preferably from 2 mm to 15 mm.

[0043] The overlap between stripes can be 0.02 mm to 0.20 mm, preferably 0.03 mm to 0.17 mm, and more preferably 0.05 mm to 0.15 mm.

[0044] Preferably, the direction of the stripes is changed between each layer of molten powder. Preferably, the angle of change of direction is 60° to 70°.

[0045] Furthermore, the overlap between the molten channels can be from 0.010 mm to 0.800 mm, preferably from 0.015 mm to 0.170 mm, and more preferably from 0.020 mm to 0.150 mm.

[0046] Preferably, the selective laser melting step is carried out in an inert gas atmosphere, such as nitrogen or argon. An inert atmosphere particularly allows for the prevention of trace amounts of moisture and oxygen that could affect the mechanical properties of the component.

[0047] The melting parameters just described allow for the production of untreated solid parts with the desired shape.

[0048] In step S3, the untreated solid component may be subjected to heat treatment, preferably vacuum heat treatment, or alternatively, under the partial pressure of an inert gas such as nitrogen.

[0049] The heat treatment step S3 is carried out at a first temperature T1 of 900°C to 1300°C, preferably 1000°C to 1200°C, and more preferably 1100°C to 1150°C.

[0050] In the heat treatment step S3, the solid component is subjected to a first temperature T1 for 30 minutes to 4 hours, preferably 45 minutes to 1 hour and 30 minutes.

[0051] After heat treatment step S3, an intermediate solid component is obtained.

[0052] Advantageously, heat treatment step S3 provides the elimination of residual stress in the component, homogenization of the local chemical composition of the component, and replacement of harmful phases in the solid solution. Furthermore, during the cooling process after heat treatment, the desired hardened phase precipitates at a suitable size and in a good quantity.

[0053] Then, the intermediate solid component is subjected to a tempering step S4, which can be performed according to two possible alternatives.

[0054] In the first alternative, the intermediate solid component is subjected to a tempering step S4a, wherein the intermediate solid component is subjected to a second temperature T2 of 700°C to 1000°C, preferably 820°C to 880°C, more preferably 830°C to 850°C.

[0055] In the tempering step S4a of the first alternative, the solid component is subjected to a second temperature T2 for a second duration of 30 minutes to 8 hours, preferably 1 hour to 5 hours, and more preferably 2 hours to 4 hours.

[0056] In the second alternative, the intermediate solid component is subjected to a second alternative tempering step S4b, wherein the intermediate solid component is subjected to a third temperature T3 of 670°C to 770°C for a third duration, and then subjected to a fourth temperature T4 of 570°C to 670°C for a fourth duration.

[0057] Preferably, the third temperature T3 can be from 680°C to 750°C, more preferably from 700°C to 730°C. The third temperature T3 remains constant throughout the entire third duration, which can be from 6 hours to 20 hours, preferably from 7 hours to 19 hours, more preferably from 7 hours and 30 minutes to 8 hours and 30 minutes.

[0058] Preferably, the fourth temperature T4 can be from 590°C to 735°C, more preferably from 605°C to 730°C. The fourth temperature remains constant throughout the fourth duration, which can be from 6 hours to 10 hours, preferably from 7 hours to 9 hours, more preferably from 7 hours and 30 minutes to 8 hours and 30 minutes.

[0059] Preferably, the cooling between the third temperature T3 and the fourth temperature T4 is carried out in air at a cooling rate of 50°C ± 20°C per hour. This rapid cooling allows for the prevention of precipitation of harmful phases and allows the alloy to harden via the precipitation of hardening phases.

[0060] After one of the alternative tempering steps is completed, a final solid part is obtained, which has the following mechanical properties: The hardness is greater than or equal to 20 HRC (according to the Rockwell C scale), preferably greater than or equal to 25 HRC; this hardness is determined according to standard ISO 6508; According to ASTM standards, the grain size is 1 to 15; preferably, according to ASTM standards, the grain size is 3 to 11; the grain size is determined according to standard ASTM E112. At 20°C, the tensile strength Rm is greater than or equal to 900 MPa (Newtons per square millimeter), preferably greater than or equal to 1100 MPa; the tensile strength is determined according to standard ISO EN-2001; At 20°C, the yield strength Rp0.2 is greater than or equal to 600 MPa, preferably greater than or equal to 700 MPa; the yield strength is determined according to standard ISO EN-2001. At 20°C, the elongation at break is greater than or equal to 8%, preferably greater than or equal to 10%; the elongation at break is determined according to standard ISO EN-2001; and / or At 200℃, the average linear expansion coefficient is 9×10⁻⁶. -6 / ℃ to 11×10 -6 / ℃, preferably 9.5×10 -6 / ℃ to 10.5×10 -6 / ℃; at 600℃, the average linear expansion coefficient is 11×10. -6 / ℃ to 13×10 -6 / ℃, preferably 11.5×10 -6 / ℃ to 12.5×10 -6 / ℃; the average coefficient of thermal expansion was determined using a dilatometer according to standard NF EN ISO 17562.

[0061] Compared to components manufactured using existing methods (whether forging, casting, or selective laser melting), solid components obtained using the method of this invention exhibit improved mechanical properties. Advantageously, these mechanical properties are maintained even under extreme temperatures and conditions, such as when the components are used in aircraft propulsion systems.

[0062] Solid components manufactured using the aforementioned method may be selected from components used in, for example, fuel injection systems, combustion chambers, turbine nozzle bushings, turbine housings, and turbine blade sealing sections, and are free from macroscopic cracks, particularly those with a size greater than 300 μm. Detailed Implementation

[0063] According to an example embodiment of the method of the present invention, turbine housings with diameters ranging from 300 mm to 1500 mm were manufactured.

[0064] For this purpose, in step S1, powder is prepared by atomizing Inconel 783.

[0065] The obtained powder has the same composition as the initial alloy, and additionally contains 0.025% by weight of oxygen, 0.02% by weight of nitrogen and 0.001% by weight of hydrogen.

[0066] In step S2, the powder is used for selective laser melting.

[0067] Step S2 is performed in an argon atmosphere, using the following parameters: Laser power = 300 W; Laser scanning speed = 1200 mm / s; Powder layer thickness = 40 μm; Laser melting channel width = 150 μm; Stripe width = 2 mm; and The angle of change of the stripe direction from one layer to another is 67°.

[0068] Then, an untreated solid component is obtained. This component has the same composition as the initial alloy, but additionally contains 0.035 wt% oxygen, 0.025 wt% nitrogen, and 0.005 wt% hydrogen.

[0069] In step S3, the untreated solid part is subjected to air quenching heat treatment.

[0070] The heat treatment step S3 is carried out at a first temperature T1 of 1107°C to 1121°C. Step S3 is performed in air for 1 hour according to standard AMS2750, followed by tempering step S4a.

[0071] This yields a final solid component, which has the following characteristics: Hardness greater than 25 HRC; According to the standard ASTM, the grain size is 3 to 11, with an average of 5 ASTM. At 20℃, the tensile strength Rm is 1100 MPa; At 20℃, the yield strength Rp0.2 is greater than 700 MPa; At 20°C, the elongation at break is greater than 10%; and At 200℃, the average linear expansion coefficient is 10±0.3, and at 600℃, the average linear expansion coefficient is 12±0.3.

[0072] The comparative solid component obtained using this method exhibits optimized properties compared to a component manufactured using the same method but with Inconel 718 as the initial alloy. Specifically, the comparative solid component has an average linear expansion coefficient of 13 ± 0.3 at 200 °C and an average linear expansion coefficient of 15.5 × 10⁻⁶ at 600 °C. -6 / ℃ ± 0.3 × 10 -6 / ℃.

[0073] Therefore, the method according to one embodiment of the present invention improves the average linear expansion coefficient by about 30% compared with the selective laser melting method in the prior art.

Claims

1. A powder for manufacturing parts by selective laser melting, said powder being prepared by atomizing an initial cobalt alloy comprising 22% to 45% cobalt, 20% to 35% nickel, and 18% to 32% iron, said powder having the following particle size distribution: D10 size is less than 25 μm. The D50 size ranges from 20 μm to 50 μm, and The D90 size is less than 80 μm.

2. The powder according to claim 1, wherein, The alloy additionally contains 2.0% to 4.0% by weight of chromium, 2.0% to 4.0% by weight of niobium, and 4.0% to 7.0% by weight of aluminum.

3. The powder according to claim 1 or 2, wherein, The cobalt alloy comprises, by weight percentage: 2.5% to 3.5% chromium, 26.0% to 30.0% nickel, 24.0% to 27.0% iron, 2.5% to 3.5% niobium, 5.0% to 6.0% aluminum, and 33.5% to 42.5% cobalt.

4. The powder according to any one of the preceding claims, wherein, The cobalt alloy is Inconel 783.

5. A method for manufacturing a component, the method comprising the following steps: S1: Prepare the powder according to any one of claims 1 to 4; S2: The powder is melted by selective laser melting to obtain a solid component.

6. The method of claim 5, further comprising: The solid component is subjected to heat treatment step S3 at a first temperature T1 of 900°C to 1300°C.

7. The method according to claim 5 or 6, further comprising a first alternative tempering step S4a, in which the solid component is subjected to a second temperature T2 of 700°C to 1000°C.

8. The method according to claim 5 or 6, further comprising a second alternative tempering step S4b, in which the component is subjected to a third temperature T3 of 670°C to 770°C and held for a third duration, and then subjected to a fourth temperature T4 of 570°C to 670°C and held for a fourth duration.

9. The method of any one of claims 5-8, wherein, Step S2 is performed at a laser power of 100 watts to 1000 watts.

10. The method of any one of claims 5 to 9, wherein, Step S2 is performed at a laser scanning speed of 700 mm / s to 1300 mm / s.

11. A solid component obtained by the method according to any one of claims 5 to 10, comprising: A hardness of 20 HRC or higher, preferably 25 HRC or higher, and / or Grain size of 1 ASTM to 15 ASTM, preferably 3 ASTM to 11 ASTM, and / or Tensile strength greater than or equal to 900 MPa, preferably greater than or equal to 1100 MPa.

12. An aircraft comprising one or more solid components according to claim 11 or solid components obtained by the method of any one of claims 5 to 10, said components being selected from components used in fuel injection systems, combustion chambers, turbine nozzle bushings, turbine housings, and turbine blade sealing sections and free from macroscopic cracks.